Dalley and the Malayan Security Service, 1945-48 : MI5 vs. MSS - Comber, Leon (Book collections on Project MUSE., 2018)
This book fills an important gap in the history and intelligence canvas of Singapore and Malaya immediately after the surrender of the Japanese in August 1945. It deals with the establishment of the domestic intelligence service known as the Malayan Security Service (MSS), which was pan-Malayan covering both Singapore and Malaya, and the colourful and controversial career of Lieutenant Colonel John Dalley, the Commander of Dalforce in the WWII battle for Singapore and the post-war Director of MSS. It also documents the little-known rivalry between MI5 in London and MSS in Singapore, which led to the demise of the MSS and Dalley's retirement.